Cost–benefit analysis of retrospectively identifying missed compensable billings in the emergency department. (12th June 2020) - Lim, Andy; Lim, Alvin
Abstract : A cost–benefit analysis at an Australian metropolitan ED demonstrates that it is financially sound to retrospectively identify missed compensable billings. Abstract: Objective: The aim of the present study was to perform a cost–benefit analysis of retrospectively identifying missed compensable billings in a public Australian ED. Methods: A retrospective review of patients who were eligible for billing from the period of 1 April 2018 to 31 January 2019 was undertaken. Individual patient files were examined and reconciliated with the historical billing record and any discrepancies identified. Financial modelling with Vose ModelRisk and R Studio v1.2.5033 was employed to estimate future benefits of such a strategy. Uncertainty analyses included variation in wage cost (AU$0–200/h), discount rate (3–10%), presentation growth rate, percentage compensable, benefit recovered/patient, percentage recoverable and cost per patient. Results: A total of 76 523 patients presented during this time. Of these, 2737 patients were deemed compensable. A total of 740 undocumented billing items were identified with an estimated Medicare Benefits Schedule value of $59 870 and an Australian Medical Association value of $152 400. The net present value (NPV) of this identified cash flow stream in perpetuity was $1 436 892 (Medicare Benefits Schedule) and $3 657 600 (Australian Medical Association) (i.e. the total value of recovering this amount of money each year indefinitely, corrected for the time value of money). The positive NPV was maintained with sensitivity analysis. Conclusion: All scenarios examined led to a positive NPV favouring retrospectively identifying missed compensable billings.